2019
DOI: 10.1016/j.bbrep.2018.12.009
|View full text |Cite|
|
Sign up to set email alerts
|

Rapamycin suppresses postnatal muscle hypertrophy induced by myostatin-inhibition accompanied by transcriptional suppression of the Akt/mTOR pathway

Abstract: Myostatin (MSTN) is a well-known negative growth factor of muscle mass, and studies have shown that MSTN-inhibition would be a potential strategy to treat muscle atrophy seen in various clinical conditions. Recent studies suggest that MSTN-inhibition induces skeletal muscle hypertrophy through up-regulation of the anabolic Akt/mTOR pathway. Therefore, it was hypothesized that the muscle hypertrophy induced by MSTN-inhibition would be suppressed by the administration of rapamycin (RAP), a mTOR suppressor. A MST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…MyoD1 and Myf5 are involved in muscle determination, while Myog plays a predominant role in muscle cell differentiation to form muscle fibers. MRF4 is essential in the maintenance of postnatal muscles (49). MSTN is a negative regulator of skeletal muscle growth (50).…”
Section: Discussionmentioning
confidence: 99%
“…MyoD1 and Myf5 are involved in muscle determination, while Myog plays a predominant role in muscle cell differentiation to form muscle fibers. MRF4 is essential in the maintenance of postnatal muscles (49). MSTN is a negative regulator of skeletal muscle growth (50).…”
Section: Discussionmentioning
confidence: 99%
“…Myostatin negatively controls muscular growth [106]; therefore, the repression of the myostatin signaling pathway inhibits the transcription of genes implicated in protein synthesis, stimulating muscular anabolism by means of the regulation of the Akt/mTOR pathway [90,107,108]. The transcriptional modulation of components of the Akt/mTOR pathway (Akt, p70S6K, and 4E-BP1), as well as of the myogenic regulator factor Mrf4, are involved in the increase of the musculoskeletal mass induced by the suppression of myostatin [109]. The apparent enlargement of muscle-cell size is due, in part, to the phenomenon of “cell swelling”, due to the osmotic changes, this event is experienced by the rapid contraction fibers.…”
Section: Physical Exercise and Redox Responsementioning
confidence: 99%
“…This certainly gave the impression that activation of mTORC1 signaling was desirable for the maintenance of muscle mass. Most recently, it was shown that rapamcycin treatment inhibited muscle mass increase caused by myostatin loss (19). Thus, it seemed reasonable that inhibition of the pathway was not desirable in settings of muscle loss (1, 18, 20).…”
Section: Introductionmentioning
confidence: 99%